2, 4-Diarylamino-pyrimidines as kinase inhibitors co-targeting IGF1R and EGFRL858R/T790M. Issue 19 (1st October 2015) - Chan, Shingpan; Han, Kun; Qu, Rong; Tong, Linjiang; Li, Yingjun; Zhang, Zhang; Cheng, Huimin; Lu, Xiaoyun; Patterson, Adam; Smaill, Jeff; Ren, Xiaomei; Ding, Jian; et al.
Graphical abstract